Human talent as competitive factor at touristic activity in Metropolitan Lima - Ríos Delgado, Teresa Jesús (2019)
Tourism has been growing in our country, specifically at Metropolitan Lima since it houses a significant part of touristic services: travel agencies and tour operators, lodgings, touristic transportation, touristic restaurants, etc. Touristic companies as every single organization is made up of people, becoming the most value resource in the organization. Our objective was to analyze human talent based on its competences, abilities, updated training, incentives y recognitions, because they are the starring and leaders in achieving the business´s objectives and goals. As main conclusion, it was founded that even though human talent is a competitive factor, it is not recognizable its importance since it is not potentiated in the organizational objectives of the company.